Researching Sustainable Communication: Constructively Critiquing Human Resource Management Communication Practices - Ditlevsen, Marianne Grove; Kastberg, Peter (Communication & Language at Work, 2024)
Ditlevsen and Johansen (2024) introduce in this issue the theoretical concept of sustainable communication as a response to a general call for a responsibilization of communication itself. Sustainable communication refers to communication practices that benefit not only organizations but also people and society at large. Moreover, Ditlevsen and Johansen (2024) present and discuss an integrated framework for sustainable communication – a framework that is based on three distinct yet interrelated mindsets, i.e., the ethical, the reflexive, and the critical, to be used for addressing communication as a responsible organizational function. Based on this, it is the aim of this paper to put forward and discuss illustrative examples of human resource management (HRM) communication practices through the lenses of sustainable communication. Three studies on HRM communication practices with a focus on the discursive construction of the employee (Kastberg & Ditlevsen, 2010; 2022; 2023) serve as the empirical basis. The re-reading and discussion of the three studies follow the methodological framework for doing critical research proposed by Alvesson and Deetz (2021). Following this framework, this paper offers 1) insights, i.e., the outcome of an interpretation and a hermeneutic understanding of the empirical data, 2) critique, i.e., a discussion of the presented insights to expose hidden, taken-for-granted assumptions within the field of HRM, and 3) a transformative redefinition, i.e. “the development of critical, socially relevant knowledge and practical understanding that enable change and provide skills for new ways of operating” (Alvesson & Deetz, 2021, p. 19). By re-reading and discussing the three studies, it is shown that superimposing the tenets of sustainable communication onto everyday instances of HRM communication can shed new light on known issues and point to much-needed ethical, reflexive, and critically oriented avenues of research. The paper funnels into a discussion of what the implications of the insights gained and the critique offered could be for practice, including specific suggestions for practicing sustainable communication within the field of HRM communication. These suggestions take the form of concrete transformative redefinitions.